First principles study on the electronic and optical behavior of atomically thin MXene/MC (M = Si, Ge) heterostructures - Tao, Binbin; Zhu, Zhengyang; Li, Jianping (Frontiers in Physics, 2025)
Following the discovery of graphene, research on two-dimensional (2D) materials has surged. To enhance the performance and broaden the applications of these materials, heterostructures are formed by stacking two different layered materials through van der Waals (vdW) interactions. This study, based on first-principles calculations, explores the intriguing properties of heterostructures made from Zr2CO2, SiC, and GeC monolayers. The results indicate that the Zr2CO2/SiC and Zr2CO2/GeC vdW heterostructures retain their original band structure and exhibit robust thermal stability at 300 K. Additionally, the Zr2CO2/MC heterostructure, with an I-type band alignment, shows promise as a light-emitting device material. Charge transfer between Zr2CO2 and SiC (or GeC) monolayers are obtained as 0.1459 |e| and 0.0425 |e|, respectively. The potential drop across the interface for Zr2CO2/SiC and Zr2CO2/GeC is 6.457 eV and 3.712 eV, respectively. Besides, the Zr2CO2/SiC vdW heterostructure presents excellent carrier mobility along the transport direction (about 3656 cm2 V−1·s–1). These heterostructures exhibit remarkable optical absorption, further demonstrating the potential of Zr2CO2/MC for optoelectronic applications. This study provides valuable theoretical insights for designing photocatalytic and photovoltaic devices using heterostructures.